Development of a prototype model for fully automated Sarawak layered cake machine - Ana Sakura, Zainal Abidin; Annisa, Jamali; W., K. Tan; Andrew Ragai Henry, Rigit; J., S. Chong; M. A., Kiprawi; Johnapi, P. R. (2014)
Layered cake also known as kek lapis is very synonym to Sarawak and very famous souvenir to tourist who travels to Sarawak. The exclusive savour and colourful layered design attribute has secure its constant demand all the year especially during festive seasons. The products are not only catered for Sarawak but also exported to Peninsular Malaysia, Singapore and Brunei. The industry contributes almost RM 3 million a year to the entrepreneurs. However, the tedious traditional process is unable to cope with the demand. Manual process is highly dependent on labours and the labours skills has direct influence on the quality of cakes produced. The development follows systematic engineering design process. Concept of sectional base mechanism has been chosen for the machine. The automatic machine has includes all basic processes namely filling of mixture to the baking tray, baking, layered, pressing and cooling. The proposed model is expected to produce 216 moulds per day, which is 430% improvement from the current production rate (50 moulds). Estimated manufacturing cost is about RM 37,000 only. Copyright © 2014 BICET –All right reserved.